The absorption spectrum and absolute absorption cross sections of acetylperoxy radicals, CH3C(O)O2 in the near IR. (April 2020) - Rolletter, Michael; Assaf, Emmanuel; Assali, Mohamed; Fuchs, Hendrik; Fittschen, Christa
Highlights: Absorption spectrum of acetylperoxy radicals in the near infrared has been measured. Determination of absolute absorption cross sections for CH3 C(O)O2 radicals. Better selectivity can be achieved in near IR compared to UV absorption. Detection limit of < 4 × 10 11 cm −3 can be achieved in time resolved measurements. Abstract: The Ã- X ˜ electronic transition of acetylperoxy radicals (CH3 C(O)O2 ) in the near-infrared was measured at 67hPa synthetic air in the spectral ranges from 6094 cm −1 to 6180 cm −1 and 6420 cm −1 to 6600 cm −1 . CH3 C(O)O2 radicals were generated by the pulsed photolysis of a acetaldehyde/Cl2 /O2 mixture at 351 nm and subsequently measured by time-resolved continuous-wave cavity ring-down spectroscopy (cw-CRDS). The absorption cross sections of eight discrete absorption lines were determined relative to the absorption cross section of HO2, which has previously been reported. The strongest absorption cross section was found at 6510.73 cm −1 and was determined to be (4.9 ± 2.5) × 10 −20 cm 2 .